Informality, saving and wealth inequality in Colombia (2015)
ABSTRACT: The informal sector is an extensive phenomenon in developing countries. While some of its implications have drawn considerable attention in the literature, one relatively unexplored aspect has to do with the saving patterns of workers and firms and how these might influence aggregate savings and wealth inequality. This paper aims to fill that gap by examining both entrepreneurs’ and workers’ choices regarding whether to perform informally and regarding asset accumulation. Specifically, the paper builds an occupational choice model wherein saving is primarily motivated by precautionary considerations. The model features labor and capital market segmentation, and it is calibrated to replicate the saving rates, wealth inequality and composition of occupations across the formal and informal sectors of Colombia. Computational experiments additionally make it possible to analyze the effects of highly debated formalization policies on wealth redistribution and promotion of saving and entrepreneurship. Alternative frameworks are finally considered.